Reinventing Nature to Develop Ecoglogical Virtues - Bagchi, Jyoti Prakash (JOURNAL OF INDIAN EDUCATION, 2010)
The Ecological unrest of modern times is simply because of an aggravation of the earnest desire to conquer over nature and presence of extreme of logical positivist approach. The paper underlined the causes that plagued our understanding of nature. It argues that promotion of environment virtues cannot be just attained by transmitting the broad spectrum of scientific knowledge or ‘indoctrination’ rather students must be provided genuine opportunity to reinvent nature.